THE IMPACT OF ADMINISTRATION OF GUMITIR FLOWER SIMPLICIA OINTMENT ON COLLAGEN TISSUE DENSITY IN THE HEALING OF WHITE RAT BURNS - I Gede Yoga Sukya Sumantara; I Wayan Gorda; Ida Ayu Pasti Apsari; I Made Merdana; Ida Bagus Oka Winaya (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Burns are a form of damage or loss of skin tissue caused by direct contact with heat sources such as fire, hot water, electricity and radiation. The wound healing process is not only limited to local regeneration processes, but is also greatly influenced by endogenous factors such as age, nutrition, immunology, use of drugs. One of the medicines made from nature is gumitir flowers. Gumitir flowers contain antioxidants which can help the healing process of burn wounds. This research was conducted with the aim of determining the effectiveness of administering gumitir flower simplicia ointment on collagen density in white rats that had suffered burns. In this study, 24 male Wistar rats were used and divided into 4 groups using RAL (completely randomized design). Then the mice were burned using a modified soldering iron, the wounds were made on the mice's backs at a temperature of 800C for 10 seconds. The results of the study showed that there was a difference in collagen density in the skin of white mice between white mice given gumitir flower simplicia ointment with a concentration of 0% (pure vaseline) with concentrations of 12.5%, 25% and 37.5%. The conclusion of this research is that gumitir flower simplicia ointment can help the healing process of burn wounds seen from its collagen density.